Frontiers in cancer immunotherapy—a symposium report. Issue 1 (13th November 2020) - Cable, Jennifer; Greenbaum, Benjamin; Pe'er, Dana; Bollard, Catherine M.; Bruni, Sofia; Griffin, Matthew E.; Allison, James P.; Wu, Catherine J.; Subudhi, Sumit K.; Mardis, Elaine R.; Brentjens, Renier; Sosman, Jeffry A.; et al.
Abstract: Cancer immunotherapy has dramatically changed the approach to cancer treatment. The aim of targeting the immune system to recognize and destroy cancer cells has afforded many patients the prospect of achieving deep, long‐term remission and potential cures. However, many challenges remain for achieving the goal of effective immunotherapy for all cancer patients. Checkpoint inhibitors have been able to achieve long‐term responses in a minority of patients, yet improving response rates with combination therapies increases the possibility of toxicity. Chimeric antigen receptor T cells have demonstrated high response rates in hematological cancers, although most patients experience relapse. In addition, some cancers are notoriously immunologically "cold" and typically are not effective targets for immunotherapy. Overcoming these obstacles will require new strategies to improve upon the efficacy of current agents, identify biomarkers to select appropriate therapies, and discover new modalities to expand the accessibility of immunotherapy to additional tumor types and patient populations.